Valve seat angle influence on losses in valves for steam turbines - Slama Vaclav; Simurda David; Kollross Petr (MATEC Web of Conferences, 2023)
Losses in valve assemblies have a significant influence on turbines´ efficiency. Therefore, performing pressure loss analysis to enhance the valve design has always been one of the traditional issues. Valves can differ in many ways in terms of their design. This paper aims to show the influence of the valve seat angle, which is one of the characteristic design dimensions. In order to achieve this, different results from a wide range of measurements on two different models are used. Regarding the first model with a 60° valve seat angle, the measurement was performed in the Aerodynamic laboratory of the Institute of Thermomechanics of the Czech Academy of Sciences. The measurement of the second model with a 90° valve seat angle was performed in the Doosan Skoda Power experimental lab. Differences are described in the form of a total loss coefficient and a flow contraction coefficient. The results are complemented by flow fields from numerical simulations performed on both valve models using a package of ANSYS software tools.